2016
DOI: 10.1160/th16-05-0349
|View full text |Cite
|
Sign up to set email alerts
|

Patient-independent variables affecting the assessment of aspirin responsiveness by serum thromboxane measurement

Abstract: The serum TXB (sTXB) assay reflects the pharmacodynamics of platelet inhibition by low-dose aspirin. However, different studies reported variable sTXB values. sTXB assay requires whole blood incubation at 37 °C as a condition for optimal thrombin generation, arachidonic acid release and its metabolism by platelet cyclooxygenase-1 to form TXA. Access to 37 °C incubation may be variably delayed, and different methods to quantitate sTXB may contribute to variable results between different Centers. We investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Consistent with this expectation, a comparison of serum TXB 2 values in two large, multicenter cohorts of aspirin-treated patients 45 , 46 showed up to 10-fold difference in median TXB 2 levels (7 and 0.6 ng/ml in the ADRIE 46 and BOSTON 45 studies, respectively) that could not be explained by patient characteristics or analytical biases 47 . Two recent in vitro studies showed that even a minor delay in starting 37 °C incubation can time-dependently underestimate serum TXB 2 levels 17 , 48 , and thus potentially account for variable aspirin responsiveness across studies and centers. Thus, we assessed the feasibility of obtaining reliable serum TXB 2 measurements across the ARES study centers.…”
Section: Study Organization: Feasibility and Implementation Of The Sementioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with this expectation, a comparison of serum TXB 2 values in two large, multicenter cohorts of aspirin-treated patients 45 , 46 showed up to 10-fold difference in median TXB 2 levels (7 and 0.6 ng/ml in the ADRIE 46 and BOSTON 45 studies, respectively) that could not be explained by patient characteristics or analytical biases 47 . Two recent in vitro studies showed that even a minor delay in starting 37 °C incubation can time-dependently underestimate serum TXB 2 levels 17 , 48 , and thus potentially account for variable aspirin responsiveness across studies and centers. Thus, we assessed the feasibility of obtaining reliable serum TXB 2 measurements across the ARES study centers.…”
Section: Study Organization: Feasibility and Implementation Of The Sementioning
confidence: 99%
“…All samples were shipped frozen to a Core Lab, where centralized measurements were performed. Serum TXB 2 was measured by enzyme immunoassay (EIA) as previously described 17 , 23 . This EIA method has a limit of detection calculated as 80% B / B 0 of 3 ± 2 pg/ml, an inter-assay coefficient of variation of 6% ( n = 75 determinations), and has been validated against gas chromatography/mass spectrometry 17 .…”
Section: Study Organization: Feasibility and Implementation Of The Sementioning
confidence: 99%
See 1 more Smart Citation
“…It is synthesized from arachidonic acid by activated platelets and after binding to its receptor on platelets causes vasoconstriction, activation, amplification, and irreversible platelet aggregation . TxA2 is rapidly hydrolyzed non‐enzymatically to the biologically inactive form TxB2 …”
Section: Introductionmentioning
confidence: 99%
“…7,8 TxA2 is rapidly hydrolyzed non-enzymatically to the biologically inactive form TxB2. 8,9 We validated our UHPLC-MS/MS method according to the European Medicines Agency (EMA) guideline for bioanalytical method validation. 10 The method was then used in combination with light transmission aggregometry (LTA) to identify good platelet responders for the diagnosis of HIT.…”
mentioning
confidence: 99%